Chemical Characterization of The Essential Oil From Aerial Parts of Lavandula rejdalii Upson & Jury, a Medicinal Plant Endemic to Morocco. Issue 6 (1st November 2020) - Gharby, Said; Asdadi, Ali; Ibourki, Mohamed; Hamdouch, Aicha; Ainane, Tarik; Hassani, Lala Amina Idrissi
Abstract: : Lavandula rejdalii Upson & Jury ( L. rejdalii ) is a Moroccan endemic plant, known for its medicinal and aromatic properties. However, little is known about its phytochemicals. In this work, L. rejdalii was investigated for its essential oil (LREO) yield and chemical composition determined by gas chromatogra- phy (GC/FID) and gas chromatography-mass spectrometry (GC/MS). Our results revealed that LREO contained twenty-six bioactive compounds representing 93.14 % of the total LREO composition. Likewise, hydrodistillation consistently resulted in higher LREO (0.83± 0.03 %). The main compounds revealed in LREO were linalool (32.03%), carvacrol (19.61 %), camphor (11.03 %), 1, 8-cineole (9.67 %), linalyl acetate (9.02 %) and sabinene (3.81 %). L. rejdalii contained a higher level of oxygenated monoterpenes and phenols, which could be linked to impor- tant biological activities and promising potential applications as food preservatives, herbal formulations and also as disinfectants and antiseptics.